Buku Pop-Up Doa Harian Anak - Firman Adi Rozianto; Sofia Rahmawati; Annisa Maileni; Niken Kencono Ungu (Center for Intellectual Property and Technology Innovation, Universitas Sains Al-Qur'an, 2024)
Children are the future generation who play an important role in the future. The formation of a child's character is greatly influenced by their environment, especially the parents, who play a central role in educating them. However, the advancements of globalization and technology have had a negative impact on children's morals, including gadget addiction. This phenomenon highlights the need for more attention in building children's character, particularly through an educational approach that involves families, schools, and the environment. One effective way to support children's character education is by teaching daily prayers using interactive media, such as pop-up books. Pop-up books have the advantage of capturing children's attention through interactive three-dimensional visual elements. In this study, the author designed a pop-up book containing daily prayers with translations in Indonesian and English, accompanied by attractive illustrations. This book not only aims to increase children's interest in reading, but also serves as a medium to support Islamic parenting. It is hoped that this pop-up book can assist parents in familiarizing children with religious values from an early age. Thus, character education based on religiosity can help create a future generation that is faithful, pious, and of noble character.